Time and Its Adversaries in the Seleucid Empire - Kosmin, Paul J. (Harvard University Press, 2018)
Cover -- Title Page -- Copyright -- Dedication -- Contents -- Preface -- Introduction -- I. Imperial Present -- 1. The Seleucid Era and Its Epoch -- 2. A Government of Dating -- 3. Dynastic Time -- II. Indigenous Past and Future -- 4. Total History 1: Rupture and Historiography -- 5. Total History 2: Periodization and Apocalypse -- 6. Altneuland: Resistance and the Resurrected State -- Conclusion -- Abbreviations -- Notes -- Bibliography -- List of Maps, Illustrations, and Tables -- Index